Pengembangan Alur Tujuan Pembelajaran dan Modul Ajar pada Kurikulum Merdeka di MAN 2 Padang - Christina Khaidir; Alya Rozali Ramadhani; Defi Angriani; Hanifah Hanifah (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2025)
This article discusses the implementation of the Learning Objective Flow (Alur Tujuan Pembelajaran, ATP) and Teaching Modules (Modul Ajar) within the Independent Curriculum (Kurikulum Merdeka) at MAN 2 Padang, specifically in the subject of Mathematics. The study aims to examine the development, application, and evaluation of these instructional tools in supporting the achievement of Learning Outcomes (Capaian Pembelajaran, CP) and strengthening students' character education. Using a qualitative approach with data collection techniques including observation and in-depth interviews, the findings reveal that ATP development is conducted collaboratively among teachers through the Teacher Working Group (KKG), based on the guidelines of the Independent Curriculum. The teaching modules are designed adaptively and contextually, integrating the reinforcement of the Profil Pelajar Pancasila and utilizing digital technologies. Challenges include limited preparation time, varying levels of teacher understanding, and adaptation to new pedagogical approaches. The results of this study provide valuable insights for the development of more effective and meaningful instructional tools within the implementation of the Independent Curriculum.